Power injection to AC grid with non-sinusoidal supplies - Mohibullah,; Mariun, Norman; Ahmad, Shahzad (2002)
Harmonic injection is the common problem when d.c. is inverted and fed to a.c. grid using inverters. Harmonic voltages and currents are generated on both d.c. and a.c. sides of the converters in DC/AC transmission systems. The harmonics, if not filtered out, enter the a.c. system and distort the system voltage waveform. Some of the serious harmful effects are extra losses and heating in machines, over voltages, torque pulsation in induction motors, interference in communication lines. The present paper describes the harmonic reduction using digital computer study. Optimum filter design is presented to reduce these harmonics to accepted levels. The real and reactive power at the point of common coupling is also studied.